Peranan Bunyi dalam filem seram ( bunyi persekitaran, Muzik dan bunyi Efek ) Projek Tesis : call Me - Jayree, bin Mili (Universiti Malaysia Sarawak, (UNIMAS), 2007)
The research on the sound in horror film. One research on its usage in ambiance sound, sound effect and music in building up the narrative films. In this research, the researcher emphasize on all elements of sound that can create mood in the moving picture. In additional, these research also part of understanding how the sound can manipulate those suspense and surprise elements in horror film. In this video project, the use of music, sound effect and ambiance sound and moving act as the catalyst to the sequence of events. "Call Me" is apart of the study on the usage sound elements of horror film in narrative film.